Efferent vestibular system in the toadfish: action upon horizontal semicircular canal afferents - Boyle, R (J Neurosci, 1990)
The influence of the efferent vestibular system (EVS) upon the background discharge and response dynamics of horizontal semicircular canal afferents was examined in the toadfish. In one set of experiments the EVS was activated using a behavioral paradigm; in the second, electrical shocks were applied to the efferent vestibular nucleus in the brain stem. The afferent's background discharge and responses to rotation were recorded before and during efferent stimulation. Both EVS activation paradigms gave qualitatively similar results: a facilitation of the afferent's rate, while the animal was at rest or in motion, and a reduction in response sensitivity. Afferents were not affected uniformly: low-gain, velocity-sensitive afferents were weakly influenced, while high-gain and acceleration afferents having low rates were the most excited. The afferents' phase of response was unmodified by electrical EVS stimulation. In many afferents a prominent form of response nonlinearity is discharge silencing over large portions of the stimulus cycle. Efferent-evoked rate increase was often sufficient to produce a full-cycle bidirectional response. Caloric facilitation of afferent rate confirmed that the EVS-induced sensitivity decrease was rate independent. These results show a dual action of the efferent system: (1) facilitating the afferent's rate and (2) reducing its sensitivity to adequate stimulation that may be correlated with the dual EVS synaptic innervation of the labyrinth, namely postsynaptic efferent-afferent synapses and presynaptic efferent-hair cell synapses.